Fabrication of platinum nitrogen-doped graphene nanocomposite modified electrode for the electrochemical detection of acetaminophen - Anuar, Nadzirah Sofia; Basirun, Wan Jefrey; Ladan, Magaji; Shalauddin, Md; Mehmood, Muhammad Shahid (Elsevier, 2018)
An electrochemical sensor for the determination of acetaminophen (AC) was fabricated on glassy carbon electrode (GCE) modified with platinum nitrogen-doped graphene (Pt/NGr) nanocomposite. Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV) and square-wave voltammetry (SWV) were performed to investigate the electrochemical behaviour of AC. From the electrochemical results, the synergy between platinum nanoparticles and nitrogen-doped graphene improved the interfacial electron transfer process, thus exhibited a higher catalytic performance towards the electrochemical oxidation of AC. A linear range between 0.05–90 μmol L−1 for the determination of AC was achieved with a limit of detection of 0.008 μmol L−1. The prepared sensor demonstrated acceptable reproducibility, stability and good selectivity in the presence of interferences such as ascorbic acid, p-aminophenol and dopamine. In addition, this method showed satisfactory results in commercial tablets.